(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The study was conducted to evaluate the efficacy of different management practices to control tomato fruit borer (TFB) under field condition. The field experiment was carried out with eight treatments, namely Neem oil, Mahogany oil, Fish and Fermented Gur (brown sugar), Netting, Chlorpyriphos, Emamectin Benzoate and Cartap along with untreated control in Randomized Complete Block Design (RCBD) and each treatment was replicated thrice. The study was under taken during the period from 25 October, 2017 to 06 April 2018. Data were collected on number and weight of total fruits plot-1, number and weight of total healthy fruits plot-1, number and weight of total infested fruits plot-1, fruits infestation (%) in number and weight, infestation reduction over control for number and weight, number of holes, and larvae plot-1, total yield plot-1 and marketable yield plot-1. Among the different management practices, netting provided the highest infestation reduction over control. The percent fruit infestation reduction over control (number basis) was the highest in Netting treated plot resulting 61.87%, 73.27%, 84.68% and 92.70% at four different harvests, respectively. The percent fruit infestation reduction over control (weight basis) was the highest with the same treatment resulting 61.38%, 74.26%, 88.41% and 91.71% at four different harvests, respectively. The number of holes plot-1 was also the lowest in Netting treated plot resulting 5.00, 8.00, 15.33 and 8.67 at four different harvests, respectively. The number of larvae plot-1 was the lowest with the same treatment resulting 2.00, 2.33, 3.67 and 3.00 at four different harvests, respectively. The maximum marketable yield (33.95 t ha-1) was achieved in the Emamectin Benzoate treated plot with the highest (1.46) benefit cost ratio. Bangladesh J. Agril. Res. 44(2): 339-353, June 2019